Aktivitas Antioksidan dan Evaluasi Sensori Kukis Tersubstitusi Tepung Kacang Hijau dan Tepung Kulit Buah Naga Merah - Dyah Kumalasari, Ika; Devira, Aninditta Putri (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2024)
Bad eating habits with high fat content but low fiber have been linked to the rise of degenerative diseases, and this is a main driven factor of developing high fiber and antioxidant foods. Green bean flour contains high protein and phenolic compounds such as flavonoids while red dragon fruit peel flour contains high antioxidants and fiber. The aim of this study was to investigate physico-chemical and sensory properties of cookies substituted with green bean and red dragon fruit peel flour. The flour formulations consisted of wheat flour (TT), red dragon fruit peel flour (TN), and green bean flour (TK) as follows: K1 (37.5% TT:62.5% TN), K2 (37.5% TT:62.5% TK), F1 (38% TT:47% TN:15% TK), F2 (38% TT:31% TN:31% TK), and F3 (38% TT:15% TN:47% TK) as well as control K0 (100% TT). Cookies quality was observed, including physical properties, chemical properties, and sensory properties. The results of this study showed that substitution of green bean and red dragon fruit peel flour in the cookies had significant effects on physico-chemical properties and sensory tests. Treatment F3 was the best formulation based on physical, chemical, and sensory properties with hardness (8.75 N), L* (42.28), a* (17.31), b* (22.05), volume development (29.41%), moisture content (5.68%), ash (3.56%), fat (24.47%), protein (9.47%), carbohydrate (57.38%), crude fiber (13.12%), antioxidant capacity of (49.32%), and IC50 (97.92 ppm). The results of the sensory test for F3 sample had scores for color (1.13), aroma (2.43), taste (4.27), texture (3.23), and overall liking (4.30).